Pengelolaan Perpustakaan Masjid di Era Globlasisasi Imformasi - Mustolehudin Mustolehudin (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
Historical fact proves that the Islamic civilization has experienced theheight of glory to the progress of the Muslim intellectual in the era of theAbbasid Caliphate. It was marked by respect and attention to the work ofDeputies scholars celebrated by establishing and developing the Islamiclibrary. One example is the Caliph al Ma’mun (813-833) who founded thelibrary is very grand and famous is “Bayt al Hikmah”.The majority of Indonesian population is followers of Islam, andIndonesia is a country with the largest number of Muslims in the world. Thatthe religious activities and religious Muslims in Indonesia central mosque.In Indonesia there are hundreds of thousands of mosques that spreadthroughout the archipelago.Library mosque as a place of religious literature must be managedproperly and professionally in accordance with the standard managementof the National Library of Indonesia in all things both management and thethings that are technical. One way is to use information technology.Keywords: Mosque Library, Information Technology